(untitled) (Research, Society and Development, 2021)
This paper describes the oral condition of patients admitted to the intensive care unit (ICU) of a public hospital in Manaus-Amazonas with a diagnosis of nosocomial pneumonia. A cross-sectional, quantitative study was carried out in hospitalized patients aged over 18 years, unable to self-care and with a clinical diagnosis of pneumonia. The clinical evaluation of the oral cavity was divided into two moments: initial (up to 48 hours after admission) and after 72 hours. Plaque index (PI), mucosal condition, presence or not of dental prosthesis, number of teeth present and tongue coating index were evaluated. Of the twenty patients evaluated, 60% were female and the predominant age group was between 70 and 90 years old (35%). 13 patients were on IMV (Induced Mechanical Ventilation) and 7 were on room air. There was an improvement in Plaque indexes (detection of dental biofilm) and presence of tongue coating after 72 hours, which corresponds to the performance of oral hygiene by the dentist and maintenance by the nursing team. The insertion of preventive protocols for nosocomial pneumonia, monitoring and decontamination of the oral cavity of patients in the ICU by qualified professionals are the key to reducing lung colonization by oral pathogens and, consequently, reducing the incidence of nosocomial pneumonia.